2012
DOI: 10.1149/2.061207jes
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Atomic Force Microscopy Probes from Pyrolyzed Parylene

Abstract: Conductive atomic force microscopy (AFM) probes fabricated from silicon cantilevers coated with pyrolyzed parylene C (PPC) are described. This method offers a simple, inexpensive route to conductive AFM probes made from carbon materials. Fabricated probes were used in current-sensing atomic force microscopy (CS-AFM) to image nanometer-sized, metallic features. Future applications of PPC AFM probes include measurement of in situ corrosion and scanning electrochemical-atomic force microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Parylene C was used as the deposition material and a four-step procedure was used to fabricate the carbon ring/nanopore electrode, as described previously. [33][34][35][36] Nanopipettes were placed in the deposition chamber of a parylene deposition system (PDS 2010, SCS coating, Indianapolis, IN) in an upright position and chemical vapor deposition of parylene C (PC) on the nanopipette surface was carried out with vaporizer and furnace temperature settings at 175 °C and 690 °C, respectively. PC-coated nanopipettes were then pyrolyzed at 900 °C under inert N 2 flow for 1 h to obtain pyrolyzed parylene C (PPC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parylene C was used as the deposition material and a four-step procedure was used to fabricate the carbon ring/nanopore electrode, as described previously. [33][34][35][36] Nanopipettes were placed in the deposition chamber of a parylene deposition system (PDS 2010, SCS coating, Indianapolis, IN) in an upright position and chemical vapor deposition of parylene C (PC) on the nanopipette surface was carried out with vaporizer and furnace temperature settings at 175 °C and 690 °C, respectively. PC-coated nanopipettes were then pyrolyzed at 900 °C under inert N 2 flow for 1 h to obtain pyrolyzed parylene C (PPC).…”
Section: Methodsmentioning
confidence: 99%
“…Typical electrode configurations consisted of a carbon ring (200-300 nm thickness, pyrolyzed carbon) which surrounds an open pore (200 nm radius) at the tip of a quartz nanopipette. [33][34][35][36] An example of an electrode utilized in these studies is shown in Fig. 1a.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon substrates were washed with IPA and dried under a flow of nitrogen prior to chemical vapor deposition (CVD). Pyrolyzed parylene C was prepared, as described previously. , Briefly, CVD of parylene C onto silicon or copper was carried out in a commercial deposition system (Labcoater 2/PDS 2010, SCS Coatings), with 0.5–1.0 g of dimer used per run. Parylene C films were pyrolyzed on substrates in a tube furnace (Lindberg, Riverside, MI) at 900 °C for 1 h under constant flow of nitrogen to yield films of approximately 169 nm ± 30 nm (N = 3), measured via AFM.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…13 Pyrolyzed parylene C (PPC) is a pyrocarbon utilized recently as a three-dimensional conductive carbon electrode material for nanopipettes 14 and atomic force microscopy probes. 15 However, little investigation of pyrocarbon chemical doping has been explored and investigations of pyrolytic carbon, as a component in semiconductor devices are limited. Pyrolyzed parylene C is an excellent material to construct not only planar semiconductor devices but also three-dimensional electrodes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…30 Pyrolyzed parylene C (PPC) is an alternative approach to obtain carbon electrodes, and we have previously reported characterization and subsequent use of this amorphous carbon material for electrochemical applications. 22,50,51 Herein, we describe a simple yet versatile strategy for the fabrication of multifunctional geometries of carbon electrodes and their application to SECM and SICM. Chemical vapor deposition of parylene enables batch fabrication and forms a conformal coating over planar or highaspect ratio substrates that are pinhole-free.…”
Section: Introductionmentioning
confidence: 99%